Can intergroup contact improve humanity attributions?. (21st June 2012) - Capozza, Dora; Trifiletti, Elena; Vezzali, Loris; Favara, Irene
<x xml:space="preserve">Abstract</x> In this paper, intergroup contact was evaluated as a strategy to favor outgroup humanization. We tested a double‐mediation model, in which contact is associated with both decreased salience of intergroup boundaries and the adoption of a common identity. These recategorizations, in turn, are related to lower levels of anxiety and higher levels of empathy, both emotions being proximal predictors of outgroup humanization. The model was tested using structural equation modeling in the context of different intergroup relations: Italians versus immigrants (Study 1); Northern Italians versus Southern Italians (Study 2). Supporting the hypotheses, group representations and emotions mediated the relationship between contact and humanity attributions. The practical implications of results are discussed.